The Effect Of Endometrial Scratch And Platelet Rich Plasma On Ultrasound Markers Of Endometrial Receptivity And Pregnancy Rate In Women Underwent ICSI - Muna Yaseen Al-Badrawi,; Dr. Lubna Amer Al-Anbari,; Dr. Manal Taha Al-Obaidi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: ICSI success relies on successful implantation, with 20-30% requiring a well-planned dialogue between high-quality embryo and receptive endometrium. Endometrial receptivity testing is crucial for ART success. Objectives: The study investigates the impact of endometrial scratch and intrauterine autologous platelet-rich plasma infusion on endometrial receptivity and pregnancy rate. Material and Method: This study involved 90 females randomly selected for endometrial scratch and intrauterine autologous platelet rich plasma infusion. Doppler studies were performed on ova collection and embryo transfer, assessing endometrial thickness, resistance index, pulse index, and systolic to diastolic ratio. Result: There weresignificant difference in endometrial thickness, resistance index, pulse index and systolic to diastolic ratio between study groups at day of embryo transfer P< 0.05, the comparison of ultrasound characteristics between ova pickup and embryo transfer in each group: A, B, and C. In group A and B there was a significant increase in endometrial thickness, and reduction in PI, RI, and S/D ratios. No significant changes were observed in group C. Conclusion The study suggests that endometrial scratching and platelet-rich plasma can enhance endometrial receptivity and pregnancy rate in infertile women undergoing ICS.